Comparative numerical study of the dynamics, ion beam and flow energetics of fast and slow focus modes in a 2 kJ plasma focus operated in various gases - Saw, S.H.; Damideh, Vahid; Chin, Oi Hoong; Ali, Jalil; Lee, Paul Choon Keat; Rawat, Rajdeep Singh; Lee, Sing (Elsevier, 2019)
Comparative study of fast focus mode (FFM)and slow focus mode (SFM)of INTI Plasma Focus device at 12 kV, based on Lee Model, are presented in this paper. Results of numerical experiments for D, Ne, and Ar gases at different pressure ranges show that as a rule-of-thumb, diameter-optimized SFM is considered to occur when fast plasma stream speed generated by pinch column is equal to the peak axial phase speed. SFM occurs at the high-pressure range of operation when beam ion energy is typically less than a few keV. Results of speed factor, fast ion beam energy, FPS energy, FIB damage factor, plasma footprint radius for FFM and SFM at different pressures of D, Ne, and Ar are presented. These results may be used to predict different applications of both modes: for example, the intense beam and flow energetics in FFM may be of interest in irradiation of surfaces for damage studies; whilst in SFM, the larger area of reduced intensity of plasma flow and very low energy per beam ion result in more uniform irradiation over a larger area of target. This larger more uniform area of irradiation has distinct advantages in nanophase material synthesis by diameter-optimized SFM. © 2019 Elsevier Ltd